ANALYSIS OF COMMUNITY PARTICIPATION IN FLOOD DISASTER MITIGATION AND STRATEGIES FOR ITS ENHANCEMENT IN LEGOK VILLAGE, DANAU SIPIN DISTRICT, JAMBI CITY - Nur Kholis; Marwoto Marwoto; Asmadi Sa'ad (Universitas Muhammadiyah Palembang, 2026)
This study was motivated by the high flood risk in Legok Village, Danau Sipin District, Jambi City, and the suboptimal level of community participation in flood disaster mitigation. The study aimed to analyze the forms of community participation, identify the factors influencing participation, and formulate strategies to enhance community involvement in flood disaster mitigation. A quantitative survey approach was employed involving residents of Legok Village. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using descriptive statistics, validity and reliability tests, Spearman Rank correlation, and SWOT analysis. The results indicated that community participation was at a moderate level. Motivation was the strongest factor associated with community participation, while environmental awareness, experience, government support, infrastructure, and socio-cultural environment also showed significant relationships. In contrast, knowledge was not significantly associated with participation. SWOT analysis recommended strategies including strengthening collaboration among communities and government institutions, improving disaster education, empowering local communities, promoting environmental conservation, and enhancing supporting infrastructure to improve the effectiveness of community-based flood disaster mitigation.